Design and development of wisdom-based organization model in government agencies - Morteza Moradi (مدیریت دولتی, 2015)
The importance of wisdom in managerial and organizational issues is growing. Wisdom, in addition to being the rational and moral judgment, is the most important success factor for organization. The purpose of this study is to investigate the effects of managerial dimensions on wisdom-based organization. Statistical population composed of employees in government agencies in Hamedan province (7941 staff), in which 381 employees were selected as samples. A 62-item questionnaire was designed based on Delphi technique in two rounds. In order to test the hypothesis, LISREL software and regression Model were employed. The analysis results indicated that leadership style, ethic, learning and knowledge management, judgment and decision making had a significant effect on wisdom-based organization.